Dual Identification? The Effects of English Learner (EL) Status on Subsequent Special Education (SPED) Placement in an Equity-Focused District. (June 2023) - Murphy, Mark; Johnson, Angela
This study examines the effects of English Learner (EL) status on subsequent Special Education (SPED) placement. Through a research-practice partnership, we link student demographic data and initial English proficiency assessment data across seven cohorts of test takers and observe EL and SPED programmatic participation for these students over 7 years. Our regression discontinuity (RD) estimates at the English proficiency margin consistently differ substantively from positive associations generated through regression analyses. RD evidence indicates that EL status had no effect on SPED placement at the English proficiency threshold. Grade-by-grade and subgroup RD analyses at this margin suggest that ELs were modestly underidentified for SPED during Grade 5 and that ELs whose primary language was Spanish were underidentified for SPED.